Integración de imágenes de nubes de puntos obtenidas por drones - Tippe Quintanilla, Percy Kim (Pontificia Universidad Católica del Perú, 2021)
The Lidar technology is an environment scanning method that produces point cloud images. In this work we study the use of a Kalman filter to combine point cloud images into a single unified 3D map.
Keywords: Aeronaves no tripuladas; Procesamiento de imágenes digitales; Sistemas de visualización tridimensional; http://purl.org/pe-repo/ocde/ford#1.02.00